2001
DOI: 10.1128/jb.183.11.3282-3292.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mutational Analysis of Three Allelic lsc Genes Encoding Levansucrase in Pseudomonas syringae

Abstract: In the plant pathogen Pseudomonas syringae pv. glycinea PG4180 and other bacterial species, synthesis of the exopolysaccharide levan is catalyzed by the extracellular enzyme levansucrase. The results of Southern blotting and PCR analysis indicated the presence of three levansucrase-encoding genes in strain PG4180: lscA, lscB, and lscC. In this study, lscB and lscC were cloned from a genomic library of strain PG4180. Sequence analysis of the two lsc genes showed that they were virtually identical to each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 44 publications
(55 reference statements)
2
105
0
Order By: Relevance
“…The LsdA signal peptide has the essential features of a Secdependent signal peptide. By contrast, other gram-negative bacteria, including the close relative Gluconacetobacter xylinus, secrete levansucrases by a signal-peptide-independent pathway (14,18,23,41,42,45). Some of these enzymes have been localized and are fully active in the periplasm of the native host or a recombinant E. coli strain (14,18,19,23), and the occurrence of a type II secretion pathway responsible for their transfer across the outer membrane cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LsdA signal peptide has the essential features of a Secdependent signal peptide. By contrast, other gram-negative bacteria, including the close relative Gluconacetobacter xylinus, secrete levansucrases by a signal-peptide-independent pathway (14,18,23,41,42,45). Some of these enzymes have been localized and are fully active in the periplasm of the native host or a recombinant E. coli strain (14,18,19,23), and the occurrence of a type II secretion pathway responsible for their transfer across the outer membrane cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Levansucrase secretion in gram-positive bacteria involves cleavage of signal-peptidecontaining precursors in Bacillus subtilis (43), Bacillus amyloliquefaciens (46), Geobacillus stearothermophilus (24), Paenibacillus polymyxa (7), Streptococcus salivarius (34), Actinomyces naeslundii (6), Arthrobacter nicotinovorans (36), and Lactobacillus reuteri (49). However, with the exception of LsdA, the other gram-negative levansucrases characterized so far are secreted by a signal-peptide-independent pathway; this occurs in Zymomonas mobilis (41), Erwinia amylovora (14), Rahnella aquatilis (42), Pseudomonas syringae (18,23), and Gluconacetobacter xylinus (45). LsdA is synthesized as a precursor with a 30-residue N-terminal signal peptide, which is cleaved off during transport to the periplasm, where the enzyme adopts its final conformation.…”
mentioning
confidence: 99%
“…Levan is a highmolecular-weight ␤-(2,6)-polyfructan that is thought to function as an extracellular storage compound metabolized by P. syringae during periods of nutrient deprivation (44). Levan synthesis is catalyzed by the periplasmic enzyme levansucrase, which is encoded by lscC (47). Alginate has been implicated in the virulence of P. syringae because it is involved in both epiphytic fitness and the dissemination of the bacterium in planta (36,85).…”
mentioning
confidence: 99%
“…EPS have multiple functions, including water absorption, accumulation of minerals and nutrients, and protection from hydrophobic and toxic macromolecules (14). P. syringae produces at least two EPS: (i) levan, a ␤-(2,6) polyfructan with extensive branching through ␤-(1,4) linkages; and (ii) alginate, a copolymer of O-acetylated ␤-(1,4)-linked Dmannuronic acid and its C-5 epimer, L-guluronic acid (25,28,38,49). Previous studies on EPS produced by P. syringae indicated that alginate was the major exopolysaccharide produced in planta (17).…”
mentioning
confidence: 99%